A 2020 desk review of Power Africa. (2nd December 2021) - Allela, Timothy
Abstract: Power Africa is an ongoing development intervention looking to expand electricity access in sub‐Saharan Africa (SSA). It was launched in 2013 by former US President Barack Obama and is overseen by the United States Agency for International Development (USAID). Power Africa operates as a public–private partnership (PPP). This report evaluates its progress from inception up to the end of 2019, relying on official project documentation and correspondence to make its findings. None of the project's stakeholders were interviewed during its preparation, imposing some limitations on findings. The appraisal is a strict desk review, conducted through the Organization for Economic Cooperation and Development's (OECD) six criteria for project evaluation (relevance, coherence, effectiveness, efficiency, impact and sustainability). The evaluation found the intervention's relevance to be high along the lines of theory of change, modus operandi, contextual analysis, risk analysis, and both champion and beneficiary needs. External coherence, on the other hand, raised questions. Power Africa's effectiveness emerged as adequate as per set indicators, with its efficiency proving difficult to determine given lack of access to financial statements. The intervention's impact was assessed as minimal on account of disproportionate connectivity success with solar lanterns. Potentials for injury during and after implementation were also identified. With respect to the intervention's sustainability, several issues came up as possible barriers towards its perpetuation beyond its 2030 deadline (and consequently, other goals that make up the 2030 agenda). This evaluation additionally made a few recommendations towards enhancing its effectiveness and sustainability, finally noting the sufficiency of OECD's six criteria for project evaluation for such undertakings.